Transient Electromagnetic Wave Scattering from Dispersive Anisotropic Layered Medium - Malyuskin, A.V.; Shulga, S.N. (Радиофизика и радиоастрономия, 2002)
Transient electromagnetic (EM) wave scattering from a stratified anisotropic medium with temporal and spatial dispersion is considered. The dispersive anisotropic medium is modeled by constitutive relations that involve four second rank tensor susceptibilities, containing time convolution integrals. Scalarization approach to the solution of transient EM scattering problems in layered anisotropic medium is outlined. As a practical application the physical model of the effective absorber was proposed and numerically investigated. В работе исследуется нестационарное рассеяние электромагнитных волн в анизотропной слоистой среде с пространственной и временной дисперсией. Анизотропная среда описывается материальными уравнениями типа временной свертки с ядрами восприимчивости, представляющими собой тензоры второго ранга. Предложена и численно исследована модель широкополосного поглощающего покрытия. У роботі досліджується нестаціонарне розсіяння електромагнітних хвиль в анізотропному шаруватому середовищі з просторовою і часовою дисперсією. Анізотропне середовище описується матеріальними рівняннями типу часової згортки з ядрами сприйнятливості, що являють собою тензори другого рангу. Запропонована і чисельно досліджена модель широкосмугового поглинаючого покриття.